Centromeric chromatin and its dynamics in plants. (23rd June 2015) - Lermontova, Inna; Sandmann, Michael; Mascher, Martin; Schmit, Anne‐Catherine; Chabouté, Marie‐Edith
Summary Centromeres are chromatin structures that are required for proper separation of chromosomes during mitosis and meiosis. The centromere is composed of centromeric DNA, often enriched in satellite repeats, and kinetochore complex proteins. To date, over 100 kinetochore components have been identified in various eukaryotes. Kinetochore assembly begins with incorporation of centromeric histone H3 variant CENH3 into centromeric nucleosomes. Protein components of the kinetochore are either present at centromeres throughout the cell cycle or localize to centromeres transiently, prior to attachment of microtubules to each kinetochore in prometaphase of mitotic cells. This is the case for the spindle assembly checkpoint (SAC) proteins in animal cells. The SAC complex ensures equal separation of chromosomes between daughter nuclei by preventing anaphase onset before metaphase is complete, i.e. the sister kinetochores of all chromosomes are attached to spindle fibers from opposite poles. In this review, we focus on the organization of centromeric DNA and the kinetochore assembly in plants. We summarize recent advances regarding loading of CENH3 into the centromere, and the subcellular localization and protein–protein interactions of Arabidopsis thaliana proteins involved in kinetochore assembly and function. We describe the transcriptional activity of corresponding genes based on in silico analysis of their promoters and cell cycle‐dependent expression. Additionally, barley homologs of all selected A. thaliana proteins have been identified in silico, and their sequences and domain structures are presented.